# How do you solve -36= - 8u + 6( u - 8)?

Jun 13, 2018

$u = - 6$

#### Explanation:

$\text{distribute and simplify}$

$- 36 = - 8 u + 6 u - 48$

$\text{add 48 to both sides}$

$- 36 + 48 = - 2 u$

$12 = - 2 u$

$\text{divide both sides by } - 2$

$\frac{12}{- 2} = u \Rightarrow u = - 6$

$\textcolor{b l u e}{\text{As a check}}$

Substitute this value into the right side of the equation and if equal to the left then it is the solution.

$\left(- 8 \times - 6\right) + \left(6 \times - 14\right) = 48 - 84 = - 36$

$u = - 6 \text{ is the solution}$

Jun 13, 2018

$u = - 6$

#### Explanation:

First, expand the brackets through FOIL

$- 36 = - 8 u + 6 u - 48$

Then add like $u$ terms

$- 36 = - 2 u - 48$

Isolate $u$ by taking the $- 48$ to the left side, changing its sign to positive $48$.

$- 36 + 48 = - 2 u$

Add $- 36$ to $48$ to get.

$12 = - 2 u$

You can’t have a negative answer, so you need to divide by $- 2$ on both sides. Diving two negatives gives a positive, hence

$\frac{12}{-} 2 = \frac{- 2 u}{-} 2$

$- 6 = u$